PELATIHAN MEMBATIK BAGI GURU SMA SEKABUPATEN BANTUL - Martono, - (Universitas Negeri Yogyakarta, 2011)
This training was conducted because there were some problems thatexisted in the field. The first problem is the lack of teachers' competence indeveloping Batik Design for the instruction of local content skills atschools. The second problem is the existence of Bantul Regent DecreeNumber 5 a year 2010 regarding batik as compulsory local content fromelementary to high schools in Bantul Regency. The third problem is theposition of Bantul which is very potential as the center of Batik craft thatobliges schools to take part in developing and preserving Batik culture.From the aforementioned problems, the teachers of cultural arte and skill inSMA 1 Kretek Bantul further proposed a demand to conduct training onBatik Making to develop knowledge regarding design, instructionalstrategy, and additional equipment of Batik. The purpose of this training areto develop the teachers' insight and skill in designing Batik with the mediumof clothes and wood using indigosol and naptol color, to find out theproduct of Batik craft made by cultural art and skill teachers in all seniorhigh schools in Bantul regency. The first method used in this training ispresentation; to present the insight in developing Batik design, learningstrategy of batik skill and batik finishing. The second method is demonstration,to visualize the technique of making batik from pattern, applyingwax, coloring, and wax disposal. The practical method of batik making isstarted from making pattern, applying wax, and coloring until it becomes afinished batik work. The teachers who participated in this training were ableto follow this program and understand the material presented by the teamwell. They were able to create batik work and it is expected that they canapply the Batik Instruction using the proper method according to theirchoice. Most of the training participants were weak in terms of developingbatik design and in keeping the tidiness of the wax dipper (cantingan) work.The Batik made by teachers was beautiful and it can be used as aninstruction media for creating art, as well as art work and scientific work.Teachers are expected to be able to implement the methods of batikinstruction by observing, imitating, and developing to create Batik craft. Theprovision of example along with the model as instructional media should notonly be imitated by students, but also to motivate them to create art.